Actuarial Calculation of Pension Funds Using Attained Age Normal (AAN) at PT Taspen Cirebon Branch Office: For Normal Pension - Amalia, Hana Safrina; Subartini, Betty; sukono, sukono (Indonesian Operations Research Association (IORA), 2024)
The pension program for Civil Servants (PNS) in Indonesia is managed by PT Taspen (Persero), which is responsible for ensuring the welfare of employees after retirement. One of the important components in the management of this pension fund is the actuarial calculation, which serves to determine the amount of normal contributions that must be paid by participants and the actuarial obligations that are the company's dependents. This calculation uses the right actuarial method to maintain the financial stability of the company and ensure that pension benefits can be optimally provided to participants. This study focuses on the use of the Attained Age Normal (AAN) method in calculating pension funds for pension program participants at PT Taspen Cirebon Branch Office. In addition, this study also compares the results of the AAN method calculation with another method, namely Projected Unit Credit (PUC), to see the advantages and disadvantages of each method. The AAN method calculates liabilities based on the current age of the participant, thus providing more conservative results and tending to be stable in the long term. The results showed that the AAN method produced a higher total normal contribution compared to the PUC method. Normal contributions calculated by the AAN method for participants of the PT Taspen pension program at the Cirebon Branch Office showed an increase of 2,095,355.33 rupiah at the age of 32 years. On the other hand, the PUC method produces a lower normal contribution, which is 827,843.62 rupiah for the same age. In terms of actuarial obligations, the AAN method also shows a more significant increase than PUC. These results show that the AAN method is more stable in the calculation of actuarial liabilities, although it requires larger contributions. Thus, although the Attained Age Normal (AAN) method results in higher normal contributions, it provides better assurance in maintaining the company's financial balance in the long term. This study provides a recommendation that PT Taspen can consider the AAN method as a more conservative alternative in pension fund management.